Antimicrobial, Antioxidant and Antiproliferative Activities of Novel Quinolones - BİNGÖL ÖZAKPINAR, ÖZLEM (WILEY-V C H VERLAG GMBH, 2020)
The compound (2) formed by esterification of dimethyl morpholine (1) was converted to acetohydrazide (3). Subsequently Schiff bases (4 a-d) and carboxy(thio)amide derivatives (5 a-e) were synthesized. Then 1,2,4-triazole (6 a-e), thia(oxa)zolidine (7 c,e) and thia(oxa)zol (8 c,e) derivatives were obtained by ring closure from carboxy(thio)amides. Mannich bases, which are containing quinolone were synthesized from 1,2,4-triazoles. The structures of newly synthesized compounds were illuminated by spectroscopic methods. Their antimicrobial (MIC method), antioxidant (DPPH, FRAP, and CUPRAC methods), and anticancer activities (MTT method) were examined. Results showed that most of the compounds exhibited good antimicrobial (<0.03-31.25 mu g/mL with MIC values) and antioxidant activities (IC50=0.001-0.004 with DPPH values). Also, some of the compounds have been found to have antiproliferative effects on the prostate (PC-3), liver (Hep3B), and breast (MCF-7) human cancer cells, and also these compounds did not have a cytotoxic effect on a normal cell.
Keywords: 1; 2; 4-triazole; quinolone; antioxidant; antimicrobial; anticancer activity; MANNICH-BASES; IN-VITRO; BIOLOGICAL EVALUATION; SCHIFF-BASES; DERIVATIVES; ANTIFUNGAL; ANTICANCER; DRUG; TRIAZOLOTHIADIAZOLES; 1,2,4-TRIAZOLES